Duelo prolongado y factores asociados - Estevan Burdeus, Patricia; De Miguel Sánchez, Cristina; Álvarez Álvarez, Roberto; Martín Molpeceres, Esther; Múgica Aguirre, Borja; Riestra Fernández, Ana; Gutiérrez Ruiz, Aránzazu; Sanz Venturerira, Lara; Vicente Sánchez, Fernando; García Jiménez, Gema; García Oliva, Francisco Javier; Cristóbal Saenz de Manjares, Rhut; et al. (Psicooncología, 2017)
Objective: To describe associated factors with the presence of Prolonged Grief Disorder (PGD) diagnosed by the Prolonged Grief Disorder-13 (PG-13) questionnaire between 6 and 18 months after the loss of a loved one.Method: Cross-sectional study. Adults chosen from a sample coming from primary-care services, hospices, and a home care team, all of them in Madrid. Variables from the deceased and the bereaved were collected: demographic, socioeconomic, psychiatric records, medical visits, Generalized Anxiety Disorder (GAD), Major Depressive Disorder (MDD), social perceived support and PGD diagnosed by PG-13 and Texas Revised Inventory of Grief (TRIG). Multivariate linear regression analysis was used to identify factors associated with PGD.Results: Prevalence of PGD was 7.023%. PGD was associated with female gender joblessness, low family incomes, a younger deceased, an illness not suitable for palliative care, anxiety or depression records before and after the loss, psychiatrist support, the use of psychotropic medication, increasing visits to emergency and primary care services, GAD, MDD, low social perceived support and the diagnosis of PGD using the TRIG. Multivariate linear regression showed that PGD was associated with psychiatrist support, MDD and an income under 2000 euros. Conclusions: Just a few of these risk factors can be modified by us (psychiatrist support, treatment of anxiety or depression) but by knowing them we will be able to have an early diagnosis and refer them to the appropriate resources like specific grief therapy as soon as possible.
Keywords: Grief; prolonged grief disorder; risk factor; linear models.